Impact of Parental Migration on Physical Health and Education of Left Behind Children in Gaindakot, Nepal - Shrestha, Rekha (Intellectual Journal of Academic Research, 2025)
Parental migration in Nepal affects the well-being of children left behind, impacting their physical health and education. To assess the effects of parental migration on physical health and academic status of Left Behind Children (LBC) versus Non-Left Behind Children (NLBC) in grades 4–12 in Gaindakot Municipality, Ward No. 5, East Nawalparasi. Using exploratory and descriptive design, data were collected through structured and unstructured interviews with students, parents/caretakers, and academic coordinators. Both qualitative and quantitative analyses compared health and academic outcomes between LBC and NLBC. More female students participated. Most LBC lived with extended family. LBC often consumed school canteen food instead of homemade meals, harming physical health. Migrant-parent households lacked proper study environments, negatively affecting health and academics. NLBC showed better health and academic performance than LBC. Parental migration adversely impacts LBC’s physical health and education. Enhancing family support and home study conditions, alongside targeted policies, can help improve LBC outcomes.